Creating a Coyote Cartography: Critical Regionalism at the Border - Caleb Bailey (European Journal of American Studies)
This article develops and deploys critical regionalism as a theoretical framework that enables a comparative transnational critique of North American border regions. Taking its lead from developments in the field of Postwestern Studies it incorporates critical metaphors drawn from Deleuzian philosophy in the form of nomadism and nomadic thought. Examining the nomadic traits of Coyote (the trickster) and coyote (the people smuggler), the article develops a comparative literature approach that challenges the centrality of existing discursive constructions of borders in North America as well as the disciplinary borders of “American” Studies. Through readings of depictions of Coyote and coyote in the work of Thomas King and Charles Bowden, the article suggests ways in which developing dialogue between the Mexican and Canadian borders can avoid the tendency to collapse regionalism into nationalism and respond to calls for more hemispheric approaches to the discipline.